2018
DOI: 10.3892/etm.2018.6241
|View full text |Cite
|
Sign up to set email alerts
|

Gene subtype analysis of Treponema�pallidum for drug resistance to azithromycin

Abstract: Azithromycin has been widely used for the treatment of . However, the drug resistance of for azithromycin is currently increasing. The aim of the present study was to analyze the association between gene subtypes of and drug resistance for azithromycin. The gene subtypes of were assayed by a polymerase chain reaction technique. Drug resistance of was analyzed using an antimicrobial susceptibility test. The results demonstrated that gene type presented higher drug resistance compared with and gene types of . Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the present study, resistance to macrolides was detected in different molecular subtypes, including 14d/f, 14d/g, 15d/g, 12d/f, 14b/f, 12e/a, 11d/f, 14e/f, and 6d/f. Similar to other studies, the mutations responsible for resistance to macrolides were observed in China in Subtypes 14e/f, 12d/f, 6d/f, and 11d/f [74]; in the UK, 14d/f and 14d/g [24]; in Australia, 14b/f, 14d/f, and 14d/g [76]; in Italy, 14d/g [73]; and in the US, 14d/f and 14d/g [10].…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, resistance to macrolides was detected in different molecular subtypes, including 14d/f, 14d/g, 15d/g, 12d/f, 14b/f, 12e/a, 11d/f, 14e/f, and 6d/f. Similar to other studies, the mutations responsible for resistance to macrolides were observed in China in Subtypes 14e/f, 12d/f, 6d/f, and 11d/f [74]; in the UK, 14d/f and 14d/g [24]; in Australia, 14b/f, 14d/f, and 14d/g [76]; in Italy, 14d/g [73]; and in the US, 14d/f and 14d/g [10].…”
Section: Plos Onesupporting
confidence: 88%
“…In the present study, nine distinct molecular subtypes of T. pallidum were found in total, including 14d/f, 14d/g, 15d/g, 12d/f, 14b/f, 12e/a, 11d/f, 14e/f, and 6d/f in 14 (51.85%), 3 (11.11%), 2 (7.40%), 1(3.70%), 2(7.40%), 1(3.70%), 2(7.40%), 1(3.70%) and 1(3.70%) of PCR-positive samples, respectively. The other studies that discovered comparable subgroups to those in our analysis include Denmark (14 d/g, 14d/f, and 14 b/f) [ 72 ], United Kingdom (14d/g and 14 d/f) [ 24 ], Argentina (14 d/f, 14d/g, and 11 d/f) [ 11 ], China (14d/f, 14e/f, 12d/f, 6d/f, 11d/f, 14b/f, 12e/a, and 14d/g) [ 15 ], Belgium (14 e/f, and 14d/g) [ 25 ], China (14d/f) [ 16 ], Italy (14d/g) [ 73 ], Denmark (14 b/f, 14 d/f, and 14d/g) [ 72 ], Peru (14d/f, 14 d/g, and 15d/g) [ 12 ], China (14d/f) [ 17 ], USA (14d/f, 14 d/g, and 15d/g) [ 10 ], China (14e/f, 12d/f, 6d/f, and 11d/f) [ 74 ], China (14d/f) [ 66 ], Taiwan (14 b/f and 14e/f) [ 75 ], France (14d/f and 14d/g) [ 14 ], USA, China, Ireland, and Madagascar (14d/f, 14 d/g, 15d/g, and 12d/f) [ 9 ], and Australia (14d/f,14d/g and 14e/f) [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mutations have already been identified in a number of countries, including China, the UK, the USA and Ireland. [27][28][29][30] The present study is the first scientific report of the occurrence of these drug-resistant mutations in Brazil. This finding contributes to the understanding of the geographical distribution of drugresistant T. pallidum strains in the world and, in particular, serves as a wake-up call for the public health surveillance service in Brazil.…”
Section: Discussionmentioning
confidence: 64%
“…The occurrence and spread of drug-resistant strains have a major impact on public health, given that these mutations can hinder the treatment of syphilis, requiring the use of macrolides, which may be in limited supply in some underdeveloped regions. 6,27,29 The high prevalence of drug-resistant T. pallidum strains in the Marajó Archipelago may be related directly to the local level of self-medication, which was reported frequently by FSWs and is a very common practice in Brazil. The extensive and indiscriminate use of antibiotics, such as azithromycin, to treat miscellaneous infections of organs such as the skin, respiratory tract and genitals, contributes to the increase in prevalence of drug-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…While syphilis can still be treated with penicillin with no occurrence of penicillin-resistant strains, there have been cases of macrolide-resistant strains, such as Azithromycin [ 6 ]. The disease’s prevalence in spite of the pathogen’s sensitivity to penicillin indicates the pathogen is unlikely to be controlled through screening and treatment alone [ 7 ].…”
Section: Introductionmentioning
confidence: 99%